The given differential equation is
"f(x,y,z,p,q)\\equiv z(p^2+q^2)+px+qy=0" ...........(1)
Which is a Charpit's equation.
Therefore , The Charpit's Auxiliary equation are
"\\frac{dp}{f_x+pf_z}=\\frac{dq}{f_y+qf_z}=\\frac{dz}{-pf_p-qf_q}=\\frac{dx}{-f_p}=\\frac{dy}{-f_q}"
"\\implies \\frac{dp}{p+p^3+pq^2}=\\frac{dq}{q+q^3+qp^2}=\\frac{dz}{-p(x+2zp)-q(y+2zq)}=\\frac{dx}{-x-2zp}=\\frac{dy}{-y-2zq}"
Taking first two fraction ,We get
"\\implies \\frac{dp}{p}=\\frac{dq}{q} \\ \\implies log(p)=log(q)+log(a)"
Where "log(a)" is a integration constant.
"\\implies \\frac{p}{q}=a" "\\implies p=aq" ........(2)
Putting the value of (2) in equation (1) ,we get
"z(a^2q^2+q^2)+aqx+qy=0"
"\\implies z(a^2q+q)+ax+y=0 \\implies q=\\frac{-(ax+y)}{z(a^2+1)}"
and "p=aq=-a\u00d7\\frac{ax+y}{z(a^2+1)}"
Now putting the value of p and q in "dz=pdx+qdy"
"\\implies (a^2+1)zdz=-a^2xdx-aydx-axdy-ydy"
"\\implies (a^2+1)zdz=-a^2xdx-ad(xy)-ydy"
On integrating ,we get
"\\frac{(a^2+1)}{2}\u00d7z^2 =-\\frac{a^2}{2}x^2-axy-\\frac{y^2}{2}+\\frac{k}{2}"
Where k is a integration constant.
"(a^2+1)\u00d7z^2=-a^2x^2-axy-y^2+k"
Which is a complete integral.
Comments
Leave a comment